MEMINIMALISIR RESIKO MORAL HAZARD PADA PEMBIAYAAN MUDHARABAH DI KOPERASI SYARIAH NURI JAWA TIMUR (KSN JATIM) PLAKPAK KECAMATAN PEGANTENAN PAMEKASAN - Dwi Agustin Maulida; Abdul Mukti Thabrani (Institut Agama Islam Negeri Madura, 2015)
Financing is carried out by the Shari’ah Financial Institutions Party, both banks and non-bank financing is very vulnerable moreover financing mudharabah that is vulnerable to moral hazard or moral deviation (reckless). Moral hazard potential is huge because of the importance of each party. Thus in the moral problem hazard will be over who should deviate, why deviate and who is harmed as the result of certain actions. Therefore, the Shari'ah financial institutions should be able to minimize the risk of loss in these high-risk financing in order to obtain profit in line with expectations and get the blessing. Based on this, which becmes the subject of this research, the first that is how the implementation of financing mudharabah in sharia’ah cooperative Nuri of East Java (KSN JATIM) Plakpak of sub-district pegantenan pamekasan. And the second how to minimize the risk of moral hazard on mudharabah financing in Shari’ah cooperative Nuri of East Java (KSN JATIM). Its first aim to know the application mudharabah in KSN JATIM and second to know how to minimize the risk of moral hazard in KSN JATIM. This research is a kind of field research. Technique of data collection includes interviews, documentation, while the analysis technique of descriptive kualitatif. Data obtained will be analyzed and described overall from the phenomena occurring in the implementation of financing mudharbah and how to minimize the risk of moral hazard on mudharbah financing in Shari’ah Cooperation Nuri of East Java. Informant is managers and financing part employees as well as customers that use of financing mudharabah. The results of field research shows that: First, Implementation of financing mudharabah in KSN JATIM in its application was in accordance with Islamic Shari'a as fulfilled pillars of mudaraba, aqid, ma'qud alaih, and, sighat. Second, how to minimize the risk of moral hazard by KSN JATIM is, to know good character, honesty, character of the customer, the customer's business should develop, analyze 6C, doing oversight or monitoring to the customer's business both on desk monitoring, and on-site monitoring